Enhancing the Added Value of Catfish through the Production and Development of Catfish Nuggets as an Alternative Food Product in Duwet Village, Tumpang District, Malang Regency - Lestari, Baroroh; Suryanto, Bambang; Amanda, Tiara Estu; Kautzar, Galuh Zuhria; Oktora, Yekie Senja; Pratama, Cahyo Ramadhan (International Journal of Social Science and Community Service, 2025)
This Community Service Program (PkM) aims to enhance the added value of catfish by processing it into nuggets as an alternative food product in Duwet Village, Tumpang District, Malang Regency. The main problems faced by the community partners include low innovation in fish processing, limited access to technology, and high unemployment among the productive age group. The activities were carried out through a series of stages including socialization, entrepreneurship training, production practice, provision of production equipment, and continuous mentoring. Evaluation methods were conducted before, during, and after the activities using interviews and questionnaires. The results of the program show that the community's skills have significantly improved, catfish nuggets were successfully developed with more hygienic and marketable quality, and entrepreneurial motivation emerged among participants. This program has a positive impact on community economic empowerment, creates new business opportunities, and supports the diversification of food products based on local potential.